A composite method for the determination of the chirality of single walled carbon nanotubes. - Meyer, R; Friedrichs, S; Kirkland, A; Sloan, J; Hutchison, J; Green, M (2003)
An approach to the unambiguous determination of the conformation of individual single walled nanotubes utilizing high-resolution transmission electron microscopy and digital image processing is described. The exit plane wave of single walled nanotubes restored from a focal series of images is used in a stepwise characterization procedure utilizing both the phase of the real space restoration and its Fourier transform. A combination of these complementary characterization steps yields an accurate measurement of the chiral vector for an individual nanotube.